2022
DOI: 10.1038/s41467-022-33366-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution silkworm pan-genome provides genetic insights into artificial selection and ecological adaptation

Abstract: The silkworm Bombyx mori is an important economic insect for producing silk, the “queen of fabrics”. The currently available genomes limit the understanding of its genetic diversity and the discovery of valuable alleles for breeding. Here, we deeply re-sequence 1,078 silkworms and assemble long-read genomes for 545 representatives. We construct a high-resolution pan-genome dataset representing almost the entire genomic content in the silkworm. We find that the silkworm population harbors a high density of geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 97 publications
1
61
0
Order By: Relevance
“…3 times lower than in S. cerevisiae. In other eukaryotes that benefit from pangenome data, the SV density scales from 1 SV/90 kb in Drosophila (Chakraborty et al ., 2019), 1 SV/38 kb in soybean (Liu et al ., 2020), 1 SV/17 kb in rice (Qin et al ., 2021) and up to 1 SV/4 kb in silkworm (Tong et al ., 2022). We also found a clear positive correlation between the numbers of SVs and SNVs/INDELs accumulating within genomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 times lower than in S. cerevisiae. In other eukaryotes that benefit from pangenome data, the SV density scales from 1 SV/90 kb in Drosophila (Chakraborty et al ., 2019), 1 SV/38 kb in soybean (Liu et al ., 2020), 1 SV/17 kb in rice (Qin et al ., 2021) and up to 1 SV/4 kb in silkworm (Tong et al ., 2022). We also found a clear positive correlation between the numbers of SVs and SNVs/INDELs accumulating within genomes.…”
Section: Discussionmentioning
confidence: 99%
“…These advancements in the ease of producing more contiguous, reference-like assemblies, has allowed few species to have multiple contiguous genomes. As expected, classical model organisms and species of anthropocentric and economic importance such as Escherichia coli (Wang et al ., 2021), Drosophila melanogaster (Rech et al ., 2022; Kim et al ., 2021), Solanum lycopersicum (tomato) (Alonge et al ., 2020), Glycine max (soybean) (Liu et al ., 2020), Oryza sativa (rice) (Qin et al ., 2021; Zhang et al ., 2022), Bombyx mori (silkworm) (Tong et al ., 2022) and humans (Audano et al ., 2019; Beyter et al ., 2021; Wong et al ., 2018) already have several contiguous genomes within each species. As has often been the case in genetics and genomics, the baker’s yeast, Saccharomyces cerevisiae , is at the forefront of the field currently totaling 68 long-read genome assemblies of non-reference strains (Abou Saada et al ., 2021; Bendixsen et al ., 2021; Berlin et al ., 2015; Czaja et al ., 2020; Istace et al ., 2017; Jenjaroenpun et al ., 2018; Lee et al ., 2022; Shao et al ., 2018; Yue et al ., 2017; Zhang and Emerson, 2019; Heasley and Argueso, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In another case, the suspected mutation (A301S in the rdl gene) did not confer measurable resistance when introduced in Plutella xylostella , suggesting that insecticide resistance is not due to this mutation alone [20]. In a tour de force association study in Bombyx mori , four genes were found to contribute to coloration, egg diapause and two silk traits, respectively, and the phenotypic effect of three of these genes was confirmed by CRISPR/Cas9 [21].…”
Section: Resultsmentioning
confidence: 99%
“…This new reference genome with an accurate structure provides a solid research foundation for further genomics and breeding. For example, an alignment-based scaffolding using a reference genome is one of the standard methods for correction and anchoring contigs to chromosome-scale assembly; the recently published genome assembly of over 500 silkworm strains was based on the method using the p50T genome assembly (Tong et al 2022). In such cases, the new Nichi01 genome assembly can serve as a better structural model.…”
Section: Resultsmentioning
confidence: 99%